Determination of heavy metals and radionuclides in coal and industrial fly ash by neutron activation analysis (NAA) and gamma spectrometry - M. AL-Areqi, Wadeeah; M. Bobaker, Aiman; Alakili, Intisar; Amran Ab. Majid,; Sukiman Sarmani, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Coal-fired power plants and industrial waste (IW) incinerators increasingly dispose large amounts of fly ash that cause environmental contamination by toxic heavy metals. This study aimed to investigate the concentration of heavy metals and measure the specific activity of naturally occurring radioactive materials (NORM) that remain in the fly ash of coal power plants and industrial incinerators. Ash samples were collected from the Kapar and Jana Manjung coal-fired power plants and the Kualiti Alam industrial incinerator in Malaysia. The concentrations of As, Ba, Co, Cr, Fe, Sb, Zn, Th and U were determined via neutron activation analysis (NAA). Results indicated that the highest concentrations of heavy metals in Kapar and Jana Manjung coal fly ash were 27 012 and 57 500 mg/kg for Fe and 494 and 1,119 mg/kg for Ba, respectively, and the lowest concentrations for Sb were at 3.67 and 2.23 mg/kg, respectively. The concentrations of Fe, Zn, Ba and Cr in industrial fly ash were 31 0007, 7 675, 2 760 and 1,029 mg/kg, respectively. The concentrations of As, Ba, Cr, Fe and Zn were higher in industrial fly ash than in coal fly ash. The specific activity concentrations of NORM, namely, 40K, 226Ra, 232Th and 238U determined by gamma spectrometry in Kapar coal fly ash were 321.65, 27.42, 134.41 and 152.71 Bq/kg, respectively. Elemental concentration results indicated that the amounts of heavy metals depended on feed sources and combustion temperatures. Most heavy metal contents and radionuclides in power plant and incinerator fly ash were significantly lower or within the global ranges.